2021
DOI: 10.2147/ceor.s325094
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of a Proteomic Test for Preterm Birth Prediction

Abstract: Background Preterm birth (PTB) carries increased risk of short- and long-term health problems as well as higher healthcare costs. Current strategies using clinically accepted maternal risk factors (prior PTB, short cervix) can only identify a minority of singleton PTBs. Objective We modeled the cost-effectiveness of a risk-screening-and-treat strategy versus usual care for commercially insured pregnant US women without clinically accepted PTB risk factors. The risk-scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…This study builds upon a previously published modeling study [30], wherein the authors constructed a decision-analytic/Markov cost-effectiveness model evaluating a test-and-treat strategy that used the risk predictor to identify patients at higher risk of PTB, followed by multimodal intervention. These authors found that the test-and-treat strategy was dominant in most scenarios.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study builds upon a previously published modeling study [30], wherein the authors constructed a decision-analytic/Markov cost-effectiveness model evaluating a test-and-treat strategy that used the risk predictor to identify patients at higher risk of PTB, followed by multimodal intervention. These authors found that the test-and-treat strategy was dominant in most scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…However, these traditional approaches are limited by the fact that risk factors only capture a small percentage (approximately 11%) [4,5] of patients who will deliver prematurely, whereas the proteomic biomarker captures the majority (75%) of sPTBs [9]. Benefit is therefore more likely, since this approach of risk identification holds promise if it identifies a much larger proportion of those destined to deliver prematurely, and intervention or combination of interventions appropriate for the group chosen are applied [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent cost effectiveness analysis showed that the use of a hypothetical proteomics prognostic test to identify women at risk of sPTB combined with appropriate treatment is cost-effective and may reduce total costs, while preventing sPTBs and their consequences. 74 These F I G U R E 2 Metaproteomics and metabolomics allow for the exploration of actual microbial and host function and predicted microbial taxonomy. Metataxonomic and metagenomics methods are gold standards for taxonomic analysis; however, these methods can only generate predicted functional profiles.…”
Section: Recent Advances In Metaproteomics and Metabolomicsmentioning
confidence: 99%
“…For someone without a history of PTB but a short cervix at 18 weeks’ gestation, vaginal progesterone should be offered. New approaches to identify those at high risk for PTB without a history of PTB or short cervix using proteomics from a maternal blood test is a potentially promising avenue to identifying, treating, and preventing early PTB, an enduring public health issue 8,9 …”
Section: Featured Reviewmentioning
confidence: 99%